Hydrogen-bonded organic frameworks for photocatalytic synthesis of hydrogen peroxide - Ji-Hong Zhang; Zhao-Ming Ge; Juan Wang; Di-Chang Zhong; Tong-Bu Lu (Nature Communications)
Abstract Photocatalysis provides a sustainable and environment-friendly strategy to produce H2O2, yet the catalytic efficiency of H2O2 overall photosynthesis (O2 + 2H2O → 2H2O2) needs to be further improved, especially in the absence of additional cocatalysts, photosensitizers and sacrificial agents. Here we find that hydrogen-bonded organic frameworks can serve as photocatalysts for H2O2 overall photosynthesis under the above-mentioned conditions. Specifically, we constructed a donor–acceptor hydrogen-bonded organic framework that exhibits a high photocatalytic activity for H2O2 overall photosynthesis, with a production rate of 681.2 μmol g-1 h-1. The control experiments and theoretical calculation revealed that the hydrogen-bonded organic frameworks with donor–acceptor structures can not only accelerate the charge separation and transfer but also optimize the reaction pathways, which significantly boosts the photocatalytic efficiency in H2O2 overall photosynthesis. This work provides insights into the design and development of efficient photocatalysts for overall H2O2 photosynthesis.